FAHP Based Evaluation of real-time operating system performance in Aerospace. Issue 2 (February 2019) - Liu, Yushuai; Su, Yu; Wang, Jinbo
Abstract: The real-time operating system has been gradually applied to China's aerospace industry. Due to the lack of effective evaluation methods for real-time operating system performance, this paper proposes a multi-index comprehensive performance evaluation method— the Fuzzy Analytic Hierarchy Process, possibility calculation method. This method can comprehensively evaluate and analyse the performance of embedded RTOS, and provide a reliable basis for the selection of embedded operating systems for aerospace systems.